1997
DOI: 10.1128/jcm.35.10.2639-2641.1997
|View full text |Cite
|
Sign up to set email alerts
|

Limited value of PCR for detection of Toxoplasma gondii in blood from human immunodeficiency virus-infected patients

Abstract: Cerebral toxoplasmosis is a common, opportunistic, and often life-threatening disease in HIV-infected patients. Diagnosis is supported mainly by clinical evidence and computerized tomography or magnetic resonance imaging scans, but brain images may share features with other brain diseases occurring in HIVinfected patients. To determine the diagnostic value of PCR for the detection of Toxoplasma gondii in blood from HIV-infected patients, we examined 89 blood samples from 59 HIV-infected patients. PCR and South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…1 Although adultacquired toxoplasmosis is usually mild to asymptomatic, the disease can be severe in the immunocopromised, leading to encephalitis. 2 In addition, the influence of sex-and pregnancyassociated hormones on the severity of T. gondii infection is of particular public health interest due to the ability of this parasite to cause congenital disease if infection occurs during pregnancy. 3 In a study of non-homosexual, human immunodeficiency virus (HIV)−positive Europeans, toxoplasmic encephalitis was found to be a more frequent acquired immunodeficiency syndrome−defining disease in females than in males.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although adultacquired toxoplasmosis is usually mild to asymptomatic, the disease can be severe in the immunocopromised, leading to encephalitis. 2 In addition, the influence of sex-and pregnancyassociated hormones on the severity of T. gondii infection is of particular public health interest due to the ability of this parasite to cause congenital disease if infection occurs during pregnancy. 3 In a study of non-homosexual, human immunodeficiency virus (HIV)−positive Europeans, toxoplasmic encephalitis was found to be a more frequent acquired immunodeficiency syndrome−defining disease in females than in males.…”
Section: Introductionmentioning
confidence: 99%
“…Those investigators detected T. gondii DNA by PCR in the blood of 9 of 13 patients (69%) with confirmed cerebral toxoplasmosis (6). Moreover, other studies (5,7,8,11) showed sensitivity values of tests with blood of between 10 and 35%. An important question is this: Why was the T. gondii PCR positive with blood from 53% of the patients with reactivated congenital corioretinitis in our study?…”
Section: Discussionmentioning
confidence: 95%
“…In clinical practice most patients with mass lesion(s) are given two weeks of treatment anyway (including patients with negative serology or a single lesion). Cerebrospinal fluid (CSF) studies, including antibody studies and polymerase chain reaction (PCR) studies, have not produced conclusive results (Franzen et al. , 1997).…”
Section: Diagnosismentioning
confidence: 99%